Manfaat Sosial Media Pada Toko zeoland.id - Deyani Faidah; Mutiara Mutiara; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
The development of technology and information which has grown very rapidly in recent years has made marketing media change little by little, social media is one example of a marketing tool that has a huge influence on the sale of a product so that the product can be recognized globally with social media. This. The visit to the Zeoland.Id store aims to fulfill one of the assignments for the Managerial Economics Course, and also aims to find out the benefits of social media at the Zeoland.Id store which can increase their sales through this digitalization. The method used in this visit was a descriptive and observative method, in which we visited the Zeoland.Id store directly and interviewed the shop owner. The results of this visit included being able to find out the tips and methods used by Zeoland.Id stores in introducing their products to consumers through social media, especially Instagram and TikTok as promotional media and Shopee as sales media, uncovering several digital marketing strategies from stores Zeoland.Id and also know the efficiency of increasing sales through social media.